An integrated experiential training programme with coaching to promote physical activity, and reduce fatigue among children with cancer: A randomised controlled trial. Issue 11 (November 2018) - Lam, Katherine K.W.; Li, William H.C.; Chung, O.K.; Ho, K.Y.; Chiu, S.Y.; Lam, H.S.; Chan, Godfrey C.F.
Highlights: Our programme promoted physical activity and reduced fatigue in cancer children. The programme also enhanced self-efficacy, muscle strengths and quality of life. The positive effects were sustained for 3 month after the whole intervention. The long-term effects of the programme require further studies. Multidisciplinary partnerships between organizations might sustain the programme. Abstract: Objective: This study examined the effectiveness of an integrated programme in promoting physical activity, reducing fatigue, enhancing physical activity self-efficacy, muscle strength and quality of life among Chinese children with cancer. Methods: A randomised controlled trial was conducted in a Hong Kong public hospital. Seventy eligible children were randomly assigned to an experimental group (n = 37) or a control group (n = 33). The experimental group received an integrated programme with 28 home visits from coaches over a 6-month period. The control group received a placebo intervention. The primary outcome was fatigue at 9 months (3 months after intervention completion). Secondary outcomes were physical activity levels, physical activity self-efficacy, muscle strength and quality of life at 9 months, assessed at baseline, and 6 and 9 months after starting the intervention. Results: The experimental group reported significantly lower levels of cancer-related fatigue, higher levels of physical activity and physical activity self-efficacy, greater right- and left-hand grip strength and better quality of life than the control group at 9 months. Conclusion: The programme is effective and feasible to implement among children with cancer and offers an alternative means of ameliorating the healthcare burden. Practice implications: Healthcare professionals should build multidisciplinary partnerships to sustain such programmes.